Teaching Legal Ethics - Susan Burns (Legal Education Review)
There is a growing body of literature in the United States and Canada which examines the place of instruction in legal ethics in the broader context of legal education. To date, there has been little consideration of this subject in Australian writing on legal education. This paper reviews the more recent literature in the area, particularly in relation to the need for instruction in legal ethics, the forms of existing tuition and the alternative course structures and teaching methodologies.